Quizlet-Assisted Microlearning Approach: Impact on Digital Literacy and Student Learning Motivation - Paijan Rambe; Nini Aryani; Emilda Sulasmi; Setya Wardana Putri (Pedagogia: Jurnal Ilmiah Pendidikan, 2026)
This study aims to examine the effect of Quizlet-assisted microlearning on digital literacy and learning motivation and investigate the mediating role of digital literacy, as well as to provide an overview of the contribution of technology-based learning media to learning competencies in the digital era. This research is motivated by the demands of education in the digital era which emphasizes the importance of digital literacy and student learning motivation. The research method uses a quantitative approach with an ex post facto design. The research sample amounted to 85 students who were selected through purposive sampling techniques. Data collection was carried out using a Likert scale questionnaire, then analyzed with Structural Equation Modeling ) based on Partial Least Square (SEM-PLS). The results of the study show that digital literacy has a positive and significant influence on learning motivation. In addition, Quizlet-assisted microlearning also has a significant effect on digital literacy and student learning motivation. Other findings reveal that digital literacy plays a partial mediator in the relationship between microlearning and learning motivation. This shows that increasing digital literacy is able to strengthen the influence of microlearning on student learning motivation. Thus, the integration of microlearning-based learning technology is an effective strategy to increase digital literacy and learning motivation, so that educators are expected to optimize the use of interactive digital media in the learning process.